Aortic regurgitation as a manifestation of giant cell arteritis. Issue 9 (September 1978) - How, J; Strachan, R W
Abstract : The detailed clinical findings of a 65-year-old woman who developed aortic regurgitation caused by giant cell aortitis are presented. The initial phase of the disease was dominated by severe non-specific constitutional symptomatology suggesting infective endocarditis or a malignancy. Aortic regurgitation as a manifestation of giant cell arteritis has hitherto recieved scant attention in the published reports. The clinical and therapeutic relevance of this masquerade is discussed.